A Comprehensive Review of Bioinks and 3D Printing: Bridging the Gap Between Innovation and Practicality (Development Engineering Conferences Center Articles Database, 2025)
Bioinks, polymer matrices printed alongside cells, simulate an extracellular matrix environment that supports cell viability and proliferation. These bioinks can be composed of hydrogels, synthetic polymers, or other specialized materials, each offering unique properties beneficial to tissue engineering and regenerative medicine. Various additive manufacturing techniques exist, but extrusion-based methods are favored for bioprinting due to their compatibility with various biomaterials. Direct Ink Writing (DIW) stands out for its precision and versatility. DIW process involves extrusion, solidification, and layer support, with theoretical underpinnings based on Deborah and Weissenberg numbers, which describe the flow behavior of the bioink. Improving nanoparticle and matric interaction yet considering cytotoxicity and cell viability during the extrusion process is a novel challenge that needs to be deeply studied. Types of particle-particle and matrix-particle forces within inks are discussed to introduce the critical concept of percolation threshold in nanomaterials and polymer matrices. This concept is essential for understanding and optimizing printed constructs' mechanical properties and functionality. Recent research highlights that viscosity modifiers enhance printability and shape fidelity but can adversely affect cell viability. Addressing these challenges is crucial for advancing the field of bioprinting and realizing its full potential in medical applications.